Mapeamento da condutividade de camadas de grafeno de diferentes espessuras usando a microscopia de força atômica condutora e espectroscopia Raman - Leal, Nazareno Nelito da Silva (2016)
The study of graphene has been one of the main areas of scientific production in physics due to its impressive properties in which they have a wide field of applications. In this way, a systematic set of methods of analysis is necessary to be able to quantify and qualify properties that are interesting for certain purposes. With the purpose of mapping the electrical conductivity in a few layers of graphene was used in this research the techniques of atomic force microscopy to have a notion of the structure of the surface studied, the Raman Spectroscopy to analyze the interaction of radiation with the carbon atoms And from it to extract useful data as well as the number of layers, intensity of the G and G 'bands and also the conductive atomic force microscopy for information about the electric current behavior in the graphene. The method to obtain the graphene was given through the technique of mechanical exfoliation in which this material is obtained from the graphite. With the obtained results it was observed the separation and identification of up to 1 layer in the samples as well as considerable current intensity measured in areas of cross sections containing greater graphene in greater and less quantity. Thus, through the techniques used in this work, it was possible to obtain information on the properties of the material, such as stacking of the layers and electrical conductivity in them.